Pieces of the Complex Puzzle of Cancer Cell Energy Metabolism: An Overview of Energy Metabolism and Alternatives for Targeted Cancer Therapy - Ghasemishahrestani, Zeinab; Melo Mattos, Larissa M.; Tilli, Tatiana Martins; Santos, André Luis Souza dos; Pereira, Marcos Dias (Current Medicinal Chemistry, 2021)
Over the past decades, several advances in cancer cell biology have led to relevant details about a phenomenon called the ‘Warburg effect’. Currently, it has been accepted that the Warburg effect is not compatible with all cancer cells, and thus the process of aerobic glycolysis is now challenged by the knowledge of a large number of cells presenting mitochondrial function. The energy metabolism of cancer cells is focused on the bioenergetic and biosynthetic pathways in order to meet the requirements of rapid proliferation. Changes in the metabolism of carbohydrates, amino acids and lipids have already been reported for cancer cells and this might play an important role in cancer progression. To the best of our knowledge, these changes are mainly attributed to genetic reprogramming which leads to the transformation of a healthy into a cancerous cell. Indeed, several enzymes that are highly relevant for cellular energy are targets of oncogenes (e.g. PI3K, HIF1, and Myc) and tumor suppressor proteins (e.g. p53). As a consequence of extensive studies on cancer cell metabolism, some new therapeutic strategies have appeared that aim to interrupt the aberrant metabolism, in addition to influencing genetic reprogramming in cancer cells. In this review, we present an overview of cancer cell metabolism (carbohydrate, amino acid, and lipid), and also describe oncogenes and tumor suppressors that directly affect the metabolism. We also discuss some of the potential therapeutic candidates which have been designed to target and disrupt the main driving forces associated with cancer cell metabolism and proliferation.
Keywords: Carbohydrate metabolism